2017
DOI: 10.18203/2319-2003.ijbcp20175697
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study to evaluate efficacy and safety of azilsartan and telmisartan in patients with grade I-II essential hypertension

Abstract: INTRODUCTIONEssential hypertension is a common cardiovascular disorder with sustained increase in blood pressure ≥140/90 mmHg. The elevated arterial pressure causes pathological changes in the vasculature and hypertrophy of the left ventricle. Hypertension is the principle cause of stroke that is a major risk factor for coronary artery disease (CAD) and its attendant complications like myocardial infarction and sudden cardiac death. It is also a major contributor to cardiac failure, renal insufficiency and dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
0
2
0
1
Order By: Relevance
“…After giving the drug orally, the prodrug azilsartan medoxomil is rapidly converted into its active form azilsartan which blocks angiotensin induced AT1 receptor activation in insurmountable fashion. [15] In the present study which was conducted as monotherapy with Azilsartan and Telmisartan in patients of essential hypertension, it was observed that both the drugs were effective in reducing both the systolic as well as diastolic blood pressure during the 12weeks study period. When the drugs were compared for their effectiveness, it was seen that both azilsartan and telmisartan are equally effective in reducing the systolic and diastolic blood pressure.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…After giving the drug orally, the prodrug azilsartan medoxomil is rapidly converted into its active form azilsartan which blocks angiotensin induced AT1 receptor activation in insurmountable fashion. [15] In the present study which was conducted as monotherapy with Azilsartan and Telmisartan in patients of essential hypertension, it was observed that both the drugs were effective in reducing both the systolic as well as diastolic blood pressure during the 12weeks study period. When the drugs were compared for their effectiveness, it was seen that both azilsartan and telmisartan are equally effective in reducing the systolic and diastolic blood pressure.…”
Section: Discussionmentioning
confidence: 57%
“…In group 1(azilsartan), mean diastolic blood pressure at 0 week was 92.37±3. 15 week when compared with the baseline systolic blood pressure. The mean diastolic blood pressure was reduced by 9.86% at the end of the study period.…”
Section: Figure 1: Consort Diagram Of the Studymentioning
confidence: 99%
“…Вместе с тем в ряде других исследований снижение АД оказалось сопоставимо в группах телмисартана и азилсартана в эквипотентных дозах (рис. 3) [57][58][59][60]. Таким образом, основываясь на всех доступных данных, можно заключить, что азилсартан и телмисартан имеют сопоставимую антигипертензивную эффективность.…”
Section: антигипертензивная эффективность телмисартана и азилсартанаunclassified